2020
DOI: 10.1002/ncp.10452
|View full text |Cite
|
Sign up to set email alerts
|

Bedside Postpyloric Tube Placement and Enteral Nutrition Delivery in the Pediatric Intensive Care Unit

Abstract: Background Enteral nutrition (EN) delivery may be more effective via a postpyloric (PP) feeding tube in critically ill children, but tube placement can be challenging. We aimed to describe PP tube placement and EN practices in a multidisciplinary pediatric intensive care unit (PICU) after the implementation of a nurse‐led bedside PP tube‐placement program. Methods In a single‐center retrospective study, we identified 100 consecutive patients admitted to the PICU for >48 hours and for whom PP tube placement was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 29 publications
0
16
1
Order By: Relevance
“…Our study showing 88% success rate of blind bedside post-pyloric tube placement in the metoclopramide group, compared with 70% in the placebo group, supports the use of metoclopramide in pediatric post-pyloric tube placement. While a previous study reported successful tube placement of 38% among the non-intervention standard group ( 22 ), our study demonstrated a higher success rate; the increase in the success rate may be contributed by the experienced tube placement operator ( 9 ). Some studies mentioned about the training years of physicians being the variable associated with successful feeding tube placement ( 11 , 15 ); therefore, the tube placement in this study was performed by one single clinician to limit this confounder.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…Our study showing 88% success rate of blind bedside post-pyloric tube placement in the metoclopramide group, compared with 70% in the placebo group, supports the use of metoclopramide in pediatric post-pyloric tube placement. While a previous study reported successful tube placement of 38% among the non-intervention standard group ( 22 ), our study demonstrated a higher success rate; the increase in the success rate may be contributed by the experienced tube placement operator ( 9 ). Some studies mentioned about the training years of physicians being the variable associated with successful feeding tube placement ( 11 , 15 ); therefore, the tube placement in this study was performed by one single clinician to limit this confounder.…”
Section: Discussioncontrasting
confidence: 73%
“…Blind bedside post-pyloric feeding tube placement has been shown to be safe and feasible for early enteral feeding in critically ill patients ( 5 , 9 ). Some studies have suggested a benefit of using a motility agent in the placement, but a definitive study, such as an RCT, has not been completed ( 10 , 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…The North American Society For Pediatric Gastroenterology, Hepatology & Nutrition (NASPGHAN) and American Society for Parenteral and Enteral Nutrition (ASPEN) suggest that the gastric route be the preferred site of enteral feeding except in cases of gastric feeding intolerance and increased aspiration risk [1,21]. Reasons for increased aspiration risk may be a past history of proven reflux or aspiration, positive pressure ventilation, intubation, neurologic deficits, or recent heart surgery, however sometimes it is patient specific and hard to define [2,22]. In our study, over 85% of participants selected gastric feeds for the patient with the most severe respiratory problems, yet respiratory status was one of the main concerns of providers when they described their decision-making process.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding complications, participants found fault with both feeding methods. A single-center prospective study found that mechanical issues were responsible for 43% of enteral nutrition interruptions for their patients, including tube malposition, obstruction, and placement failure, and postpyloric tube malfunction is especially prevalent [22,28]. Some studies found that postpyloric feeds help participants reach feeding goals more quickly and have reduced length of stay, whereas others found that gastric feeds help patients shorten the time needed to reach nutritional goals [24,29].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have therefore focused on efficient and timely placement of postpyloric tubes [35][36][37]. Success rates in postpyloric tube placement on firsttime attempt using blind-bedside placement, electromagnetic-guidance and pH guided devices vary, with some studies reporting success rates of greater than 80% with any one of these techniques [38][39][40]. Point-of-care ultrasound has now also been utilized for postpyloric tube placement with an 87-94% success rate in critically ill children, making ultrasound a promising tool for timely postpyloric tube placement [41,42].…”
Section: Gastrointestinal Dysfunction: Diagnosis and Alternative Ente...mentioning
confidence: 99%